Vivaldi as Fictional Character in "Concierto barroco" by Alejo Carpentier, Stabat Mater by "Tiziano Scarpa" and "Settecento" by Marcos Calveiro - Peñalta Catalán, Rocío (Madrygal. Revista de Estudios Gallegos, 2015)
The figure of the Italian composer Antonio Vivaldi has been very successful as a literary and film character and we can find examples of his fictionalization in works of different genre, from children’s literature to suspense novels. Our objective is to analyse how Vivaldi appears reflected as a historical character in three novels: Concierto Barroco (1974) by Alejo Carpentier, Stabat Mater (2008) by Tiziano Scarpa and Settecento (2010) by Marcos Calveiro. We shall analyse which biographic details are emphasized in each of these works and how they are presented in the plot.